2013
DOI: 10.1007/s10238-012-0227-0
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin: a key playmaker adipocytokine in non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of metabolic syndrome and can progress to cirrhosis, liver failure, and hepatocellular carcinoma. In the last two decades, the prevalence of NAFLD has been growing in most developed countries, mainly as a consequence of its close association with obesity and diabetes mellitus. The exact pathogenesis of NAFLD and especially the mechanisms leading to disease progression have not been completely understood. Adipocytes produce and secrete sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 118 publications
2
35
0
1
Order By: Relevance
“…Our observation that adiponectin was reduced at the gene expression and protein levels in the HFWDϩF/S group suggests that adiponectin may be a potential link between adipose tissue dysfunction and NAFLD progression. This hypothesis is consistent with the known role of adiponectin in modulating steatosis, inflammation, and fibrosis (9). However, further experimentation is required to determine whether a reduction in adiponectin mediates the effects of the HFWDϩF/S combination in NAFLD progression.…”
Section: Ajp-endocrinol Metabsupporting
confidence: 71%
“…Our observation that adiponectin was reduced at the gene expression and protein levels in the HFWDϩF/S group suggests that adiponectin may be a potential link between adipose tissue dysfunction and NAFLD progression. This hypothesis is consistent with the known role of adiponectin in modulating steatosis, inflammation, and fibrosis (9). However, further experimentation is required to determine whether a reduction in adiponectin mediates the effects of the HFWDϩF/S combination in NAFLD progression.…”
Section: Ajp-endocrinol Metabsupporting
confidence: 71%
“…Consistent with the above studies, our data found that circulating adiponectin levels were significantly lower in NAFLD patients compared with those in controls, and adiponectin was negatively associated with NAFLD. The study indicated that the inhibition of phosphorylation of AMP-activated protein kinase or peroxisome proliferator-activated receptor α may increase the synthesis and accumulation of hepatic lipid and glucose, as well as attenuate fatty acid β-oxidation, which made it develop into NAFLD [42].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin decrease, as well as adiponectin gene deletion, induces hepatic steatosis progression, fibrosis, and tumor development. 95 Moreover, KCs have also metabolic function, regulating fatty acids oxidation, increasing hepatic lipid storage and insulin resistance (IR), as mechanisms of adaptation to increased caloric intake. This event which is triggered by secretion of inflammatory cytokines, suggests a beneficial role for alternatively M2-activated KCs in metabolic derangements.…”
Section: Immune Cellsmentioning
confidence: 99%